Efficacy of rhizobacteria for growth promotion and biocontrol of Fusarium oxysporum and Rhizoctonia solani on wheat in South Africa - Labuschagne, Nico (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2012.